A comparative hierarchical analysis of bacterioplankton and biofilm metacommunity structure in an interconnected pond system. (14th March 2018) - Souffreau, Caroline; Busschaert, Pieter; Denis, Carla; Van Wichelen, Jeroen; Lievens, Bart; Vyverman, Wim; De Meester, Luc
Summary: It is unknown whether bacterioplankton and biofilm communities are structured by the same ecological processes, and whether they influence each other through continuous dispersal (known as mass effects). Using a hierarchical sampling approach we compared the relative importance of ecological processes structuring the dominant fraction (relative abundance ≥0.1%) of bacterioplankton and biofilm communities from three microhabitats (open water, Nuphar and Phragmites sites) at within‐ and among‐pond scale in a set of 14 interconnected shallow ponds. Our results demonstrate that while bacterioplankton and biofilm communities are highly distinct, a similar hierarchy of ecological processes is acting on them. For both community types, most variation in community composition was determined by pond identity and environmental variables, with no effect of space. The highest β‐diversity within each community type was observed among ponds, while microhabitat type ( Nuphar, Phragmites, open water) significantly influenced biofilm communities but not bacterioplankton. Mass effects among bacterioplankton and biofilm communities were not detected, as suggested by the absence of within‐site covariation of biofilm and bacterioplankton communities. Both biofilm and plankton communities were thus highly structured by environmental factors (i.e., species sorting), with among‐lake variation being more important than within‐lake variation, whereas dispersal limitation and mass effects were not observed.